Between entrepreneurs and business opportunities: The impact of the local built environment and zoning regulations on small businesses in the Netherlands - Pascal Beckers; Robert Kloosterman (European Regional Science Association (ERSA), 2010)
The Netherlands like most western countries has witnessed a strong rise in small businesses of non-western migrants in recent years. This phenomenon has been particularly observable in disadvantaged multicultural neighbourhoods of the major cities of Amsterdam, Rotterdam, The Hague and Utrecht. In the interest to stimulate commercial activities in these urban neighbourhoods, academics and policy makers alike are wondering which neighbourhood factors may contribute towards this goal. While the opportunity structures of migrant entrepreneurs are not necessarily confined to the neighbourhood, business prospects are likely to depend, next to the well-documented economic location factors, characteristics of the market, and entrepreneurs, also on the local setting. As a point of departure for uncovering relevant neighbourhood factors, we use matched pairs case study design to contrast two sets of urban residential neighbourhoods located in Amsterdam, The Hague and Utrecht, which are comparable in terms of socio-economic and demographic characteristics, but differ in terms of neighbourhood morphology and local regulations. The first set of neighbourhoods was build uniquely for residential purposes while the second set for mixed residential and commercial purposes. In the paper we discuss how these factors shape developmental prospects of firms in their start-up phase and in their later development. We combine both quantitative and qualitative methodology combining available quantitative firm data from the trade registers of the Dutch regional chambers of commerce and conducting group and individual interviews with neighbourhood experts and entrepreneurs.
Keywords: 330